Effects of thermal‐oxidative aging processes on tribological properties of polyformaldehyde and ultra‐high molecular weight polyethylene: A comparative study. Issue 7 (23rd September 2021) - Chen, Song; Wei, Lei; Cheng, Bingxue; Shi, Zhaoyao; Ding, Yuejiao; Zhang, Xiaohong; Duan, Haitao
Abstract: Using thermal‐oxidative aging and tribological experiments, effects of thermal‐oxidative aging processes on tribological properties of polyformaldehyde (POM) and ultra‐high molecular weight polyethylene (UHMWPE) were evaluated and compared with each other. It was found that the color of UHMWPE surface after aging has turned to yellow, while that of POM surface has no obvious change. The aging factors lead to dimensional change of UHMWPE disk specimens from the original circle to the ellipse in the meantime. Tribological experiments show that friction coefficients of the pairs of POM/GCr15 and UHMWPE/GCr15 tend to decrease after thermal‐oxidative aging, and the decreasing tendency in friction coefficients of POM/GCr15 is more distinct. The results of this study will contribute to the understanding of the relationship between aging and tribological properties of POM and UHMWPE, and enrich the theory of polymer tribology. Abstract :